Study on Soda−Ethanol Delignification of Pine Sawdust for a Biorefinery - Imlauer Vedoya, Camila María (2022)
The soda–ethanol process was conceived as a sulfur-free pulping process, which may also be an alternative to conventional alkaline pulping, such as kraft or soda–AQ in the biorefinery context. An in-depth study using two experimental designs was conducted to establish the viability of soda–ethanol delignification of pine sawdust. At first, a simple factorial design involving the ethanol–water ratio (ethanol:water) and the alkaline load (AL, % over dry wood, odw) was applied to define the levels of these variables and their eventual interaction. Then, a 32 experimental design was performed to evaluate the ability of the process concerning the pulping of pine sawdust. The tested conditions were carefully selected to screen a broad range of cooking times (60, 100, and 140 min) and alkaline loads (19.0, 23.3, and 27.6 %odw) to obtain pulps with different extents of delignification (residual lignin contents). Finally, the kraft, soda–AQ, and soda–ethanol treatments were compared. Soda–ethanol pulping was shown to be a suitable delignification stage for a biorefinery scheme of Pinus elliottii and Pinus taeda sawdust. It has many advantages over traditional processes regarding its environmental impact, harmless chemicals, and selectivity. The tested conditions were similar to those frequently used in conventional pulping at an industrial scale, suggesting the technical feasibility of the soda–ethanol process for pine sawdust processing.